Seasonal variation in mortality in The Netherlands. - Mackenbach, J P (1992)
STUDY OBJECTIVE--The aim was to describe the pattern of seasonal variation in all cause mortality in The Netherlands, and to analyse the contribution of specific causes of death to the winter excess of all cause mortality. DESIGN--Daily numbers of deaths in The Netherlands, by cause, were obtained for the period 1979-1987. Patterns of variation were analysed using Poisson regression. The model related the observed number of deaths to (1) the number expected for that day on the basis of person-days at risk by age and sex, (2) secular trend, and (3) first and higher order cosine terms where appropriate. MAIN RESULTS--All cause mortality has a bimodal peak in the first months of the year. After that it declines to reach a plateau in late spring. Mortality is lowest at the end of August, after which it rises steeply again. The winter excess of all cause mortality is primarily due to cardiovascular diseases (66%) and respiratory conditions (13%). Cardiovascular mortality peaks before respiratory mortality, suggesting different lag times in the effects of winter. There was an episode of exceptionally high mortality (above the normal winter excess) in early 1986, which was primarily due to cardiovascular diseases (39%) and respiratory conditions (25%). This episode was probably caused by a severe influenza epidemic, and was not followed by a compensatory lowering of mortality. CONCLUSIONS--The pattern of variation of mortality within the year suggests that it is not based on a simple relationship with climatological circumstances, because the latter fluctuate according to a less complex pattern. Cause specific data suggest an instantaneous effect of "winter" on the cardiovascular system, and a delayed effect mediated by respiratory infections.